Variation of High-Sensitivity Troponin T Results in Patients Undergoing Continuous Renal Replacement Therapy. Issue 1 (February 2019) - Srinivasan Sridhar, Vikas; Chen, Michael; Gerson, Howard; MacNamara, Elizabeth; Nessim, Sharon J.
Background: Cardiac troponins are the preferred biomarker to diagnose myocardial injury. Complicating the interpretation of serial troponins in patients with end-stage renal disease, it has been shown that the hemodialysis procedure results in a small but significant decline in high-sensitivity cardiac troponins (hs-cTnT). This raises the possibility that continuous renal replacement therapy (CRRT) might similarly alter cardiac troponin levels and affect their interpretation when cardiac ischemia is being considered. Objective: We sought to determine the effect of CRRT on hs-cTnT levels over time in a group of patients without active myocardial injury. Design: Prospective, observational study Setting: Single tertiary care hospital, Montreal, Quebec Patients: Ten critically ill patients with acute kidney injury (AKI) undergoing CRRT. Cardiac ICU (intensive care unit) patients and acute coronary syndrome patients were excluded from the study. The CRRT prescription was at the discretion of the treating intensivist and relatively high doses were used in this study. Measurements: The hs-cTnT levels were drawn pre-CRRT, within 6 hours of initiation, and approximately every 6 hours thereafter along with routine CRRT blood work. Methods: Changes in hs-cTnT, creatinine, and albumin levels were recorded over the course of CRRT. Mean change in serum analyte concentration and 95% confidence interval was determined for specified time intervals relative to baseline, with paired t tests used to determine statistical significance. Results: Among the 10 patients included in the study, the cause of AKI was primarily acute tubular necrosis from septic shock or hemorrhagic shock. Compared with baseline hs-cTnT levels prior to CRRT initiation, mean hs-cTnT level fell by 42% at 5 to 10 hours post-CRRT initiation, followed by a plateauing of levels for the duration of time on CRRT. Limitations: Single-center study only applicable to hs-cTnT assay. Conclusions: This study demonstrates a significant decrease in hs-cTnT within 5 to 10 hours of CRRT initiation. This suggests that interpretation of cardiac troponin changes during CRRT must take into consideration the timing of dialysis initiation relative to the time of sample collection.